The Prevalence of Activities of Daily Living Impairment in Patients With Heart Failure: A Systematic Review and Meta-Analysis - Lu, Jing; Wang, Meng; Zhang, Yue; Mao, Lifen; Chen, Xiaoxiao; Yin, Rulan; Shi, Xiaoqing (Frontiers in Cardiovascular Medicine, 2022)
Objectives The prevalence of activities of daily living (ADL) in patients with heart failure (HF) reported in current studies were inconsistent, ranging from 11.1% to 70.5%. The purpose of this study is to quantify the prevalence of ADL impairment in HF patients. Methods PubMed, Embase, Cochrane, CINAHL, CNKI, SinoMed, VIP and Wanfang databases were systematically searched for relevant studies (up to March 2, 2022). Cross-sectional, case-control, or cohort studies with detailed descriptions of overall ADL impairment in HF were included. Stata 16.0 was used for statistical analysis. Fixed-effect or random-effect model was adopted according to heterogeneity which was evaluated by Cochran’s Q and I2 values. Sensitivity analysis, subgroup analysis, and meta-regression were performed to investigate the sources of heterogeneity. Results A total of 12 studies with 15,795 HF patients were included in the meta-analysis, and the pooled prevalence of ADL impairment in patients with HF was 35.8% (95%CI: 25.9%-45.7%; I2=99.4%, P<0.001). No possible sources of heterogeneity were found subgroup analysis. Meta-regression indicated that assessment time might be the main source of model heterogeneity. Funnel plots and Egger’s test showed no publication bias (P=0.818). Conclusion The prevalence of ADL impairment is relatively high in HF patients. Differences in the prevalence of ADL impairment in patients with HF may be influenced by country, region, and assessment time. We suggest that more researchers could focus on the changes of ADL impairment in HF patients during different disease periods in different regions and countries.